Relationship of Public Libraries and Education in Australia: 1996-2011 - Mandana Mir Moftakhari (Türk Kütüphaneciliği)
In general, public libraries and education in all developed countries are two important items. In this study, public libraries in Australia were evaluated quantitatively based on education, the number of libraries, staff, materials, lending rates, the number of schools, teacher-student ratio, school enrollment rates and per pupil expenditure data. Findings showed that there is not a relation between public libraries and education in Australia between 1996-2011.